A Year Emergence of Covid-19 in Nigeria and Its Consequences on Educational Development of Kwara State - Dr. Tajudeen Niyi Madandola; Omotayo Salawu; Sherif Niyi Sakariyau; Oyebola Oyekemi Owolabi; Monsurat Oluwabukola Madandola (Budapest International Research and Critics University, 2021)
Corona Virus Disease 2019 simply refers to as COVID-19 is among other coronaviruses that causes respiratory infections ranging from the common cold to more severe diseases. The virus was first outbreak in Wuhan, Hubei Province, China in December 2019 but Nigeria recorded its first incidence case in Lagos State on 27th of February 2020, at exactly a year 155,076 Nigerians were infected. Kwara State of Nigeria has 2,901 confirmed laboratory tested cases, 2,268 already discharged and 51 people confirmed dead cases within a year. Interviews were conducted for selected staff and students in Kwara state. The pandemic emergence has both consequences on the educational development of Kwara state with more negative consequences like contributing to decadence of the inadequate education materials as a result of schools’ lockdown, health challenges, prolong of graduating years among others.